Search for resonant production of second-generation sleptons with same-sign dimuon events in proton–proton collisions at √s=13TeV - KAYA, MİTHAT (My University, 2019)
© 2019, CERN for the benefit of the CMS collaboration. A search is presented for resonant production of second-generation sleptons (μ~ L , ν~ μ ) via the R-parity-violating coupling λ211′ to quarks, in events with two same-sign muons and at least two jets in the final state. The smuon (muon sneutrino) is expected to decay into a muon and a neutralino (chargino), which will then decay into a second muon and at least two jets. The analysis is based on the 2016 data set of proton-proton collisions at s=13TeV recorded with the CMS detector at the LHC, corresponding to an integrated luminosity of 35.9fb-1. No significant deviation is observed with respect to standard model expectations. Upper limits on cross sections, ranging from 0.24 to 730fb, are derived in the context of two simplified models representing the dominant signal contributions leading to a same-sign muon pair. The cross section limits are translated into coupling limits for a modified constrained minimal supersymmetric model with λ211′ as the only nonzero R-parity violating coupling. The results significantly extend restrictions of the parameter space compared with previous searches for similar models.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; SPACE SCIENCE; ASTRONOMY & ASTROPHYSICS; Mühendislik (çeşitli); Fizik Bilimleri; Fizik ve Astronomi (çeşitli); Engineering (miscellaneous); Physical Sciences; Physics and Astronomy (miscellaneous)